The Relationship between Religiosity and the Bystander Effect with Prosocial Behavior in College Students - Naja, Nihayatun; Ruddin, Fajar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: In the academic environment, students are still found to have low prosocial behavior. College students are individuals in the emerging adulthood stage, the period between the ages of 18 and 29. Key characteristics of this period include identity exploration, the process of identifying and understanding oneself; instability in relationships, work, and housing; a focus on oneself; a feeling of being "in-between," meaning between adolescence and adulthood; and the development of optimism (Arnett, 2014). During this period, students are unable to commit to life choices, such as determining values, self-identity, or social roles (Arnett, 2000). This lack of commitment can negatively impact students' ability to determine social priorities. Furthermore, during this phase, students tend to be egocentric or self-centered, which can diminish their sense of responsibility or commitment to actively contributing to society. This phenomenon, as observed in Zai (2021) research, found that 40% of students chose to focus on solving their own problems and did not contribute to solving other students' problems, even though they were aware of them. Similarly, regarding the characteristics of those helped, students tend to provide assistance to individuals they know rather than anonymous individuals and to provide assistance when they are feeling well (not sad). This is in line with what Nelson & Padilla-Walker (2013) stated, stating that individuals in the identity-discovery phase but with a weak level of commitment have lower prosocial values than individuals with stable identities. In-depth identity exploration without a clear commitment can hinder individuals from behaving prosocially. Previous research still shows low prosocial values among students. Low prosocial values can be indicated by a reluctance to provide assistance to anonymous individuals, only helping when feeling well (Zai, 2021), and being indifferent to the difficulties faced by others (Badaruddin, 2021). Similarly, research by Tsalitsah et al. (2022) found that the majority of students, 51%, exhibited low social behavior. Zai (2021) study also found that the majority of students prosocial behavior was in the low category, at 43.3%. Furthermore, the researchers conducted a preliminary survey by creating a questionnaire based on the theory of Caprara et al. (2009) and distributing it via Google Form to 12 students from the faculties of psychology, engineering, health sciences, and teaching and education at Muhammadiyah University of Surakarta. The survey results showed that 33.3% of students had low levels of prosocial behavior. Low prosociality can lead to increased aggressiveness and decreased psychological well-being in students. Research by Ubaida & Avezahra, (2023) explains that individuals feel happier when involved in social activities than when engaging in activities that are solely for their own benefit. Similarly, research by Linwei et al. (2023) suggests that prosocial behavior can have a positive impact on individual happiness, such as improving life satisfaction, relationship quality, self-esteem, and mental and physical health. This study aims to examine the relationship between religiosity and the bystander effect with prosocial behavior.Methodology: This study was conducted quantitatively with a sample of 148 students. Subjects were determined using purposive random sampling with the criteria of subjects being students of the faculties of architecture, engineering, health sciences, and the faculty of teacher training and education at Muhammadiyah University of Surakarta, class of 2021-2024. The data collection method was through the distribution of Likert scale questionnaires. The scales used were The Centrality of Religiosity Scale (CRS), the bystander effect scale, and prosocialness for Adults (PFA). The data analysis method was carried out using multiple analysis techniques using SPSS version 24. Results: The results obtained a relationship between religiosity and bystander effect with prosocial behavior, indicated by the value of F = 68.351 and sig. P = 0.000 (p <0.01). Furthermore, there is a positive relationship between religiosity and prosocial behavior, as indicated by a correlation value of 0.345, and a negative relationship between the bystander effect and prosocial behavior, with a correlation value of -0.890. The results of the major hypothesis, namely that there is a correlation between religiosity and the bystander effect with prosocial behavior, are acceptable. Likewise with the minor hypothesis that there is a positive relationship between religiosity and prosocial behavior and there is a negative relationship between the bystander effect and prosocial behavior are acceptable. Based on descriptive statistical analysis, the average prosocial behavior among students from the Faculty of Teacher Training and Education, Faculty of Medicine, Psychology, and Engineering at Muhammadiyah University of Surakarta is in the high category. This is indicated by the empirical mean, which is greater than the hypothetical mean, at 65.5 > 48. Similarly, the average religiosity of UMS students from the Faculty of Teacher Training and Education, Faculty of Medicine, Psychology, and Engineering is in the high category, as indicated by the empirical mean being greater than the hypothetical mean, at 110.6 > 77.5. The average bystander effect among UMS students in the faculties of Teacher Training and Education, Faculty of Medicine, Psychology, and Engineering is classified as moderate, as indicated by the empirical mean being smaller than the hypothetical mean, at 20.7 < 27.5. In this study, the variables of religiosity and bystander effect contributed 48.6% to the prosocial variable. The bystander effect had a greater contribution than religiosity, at 37.08%. Meanwhile, religiosity contributed 11.51%.Applications/Originality/Value: These results align with research by Hafni et al. (2020) and Rubiantari & Hazim (2023), which showed that the bystander effect contributed significantly more to prosocial behavior, at 61% compared to religiosity, at 6.5%. Another study found a larger effective contribution of religiosity to prosocial behavior, at 16.7%, but with religiosity as a moderating variable (Nabila et al., 2019). This is reinforced by Darley & Batson (1973) in their experimental study, which found that prosocial behavior is more influenced by social conditions such as available time and a sense of responsibility to provide assistance to others than by an individual's religiosity. These data indicate that the bystander effect has a greater influence on the emergence of prosocial behavior. Religiosity contributes less to prosocial behavior and makes a greater contribution when placed as a moderator variable. This research has several strengths, namely the relevance of the topic discussed to current phenomena among university students and its potential contribution to social psychology regarding variables related to prosocial behavior. Furthermore, this study can serve as a reference in designing intervention programs to enhance prosocial behavior, particularly in college students. However, this study also has limitations: the results cannot be generalized to all college students because the sample size was limited to four faculties: psychology, engineering, teaching and education, and health sciences at Muhammadiyah University of Surakarta. Furthermore, this study only linked prosocial behavior to religiosity and the bystander effect, so the results obtained are less comprehensive in exploring the variables that contribute to prosocial behavior. Recommendations for future researchers include linking prosocial behavior to more factors to achieve comprehensive results. Furthermore, expanding the sample size of the study to ensure representative results for a broader population. Academics are also encouraged to consider the results of this study, as they hope to serve as a reference for the development of social sciences. In addition, it can be used as reference material in creating programs or curricula to increase prosocial behavior in students, such as by providing religious studies on campus and inserting material on the importance of prosocial behavior in religious and social subjects.